Reconciling the Empirical and the Divine: Islamic Epistemology as a Critical Lens for Positivist Teacher Assessment in Indonesia - Kamalasia Rio Nita; Mahdum Mahdum; Jimmy Copiriady; Isjoni Isjoni (Jurnal Ushuluddin, 2025)
positivism, Islamic epistemology, pedagogical assessment, and teacher performance within Indonesia's contemporary educational landscape. Drawing on a thorough philosophical analysis of positivism—from its foundational principles established by Auguste Comte to its modern interpretations and critiques—this study integrates these perspectives with the rich intellectual tradition of Islamic epistemology. By synthesizing these frameworks alongside empirical evidence from Indonesia, the paper offers a more comprehensive and contextually authentic understanding. It examines how positivist approaches have influenced pedagogical assessment methodologies while also considering how Islamic principles, embedded within the national philosophy of Pancasila and local values, provide a critical alternative and complement. Furthermore, the study assesses the implications of these intertwined approaches for fostering Higher Order Thinking Skills (HOTS) as redefined within an Islamic framework. Through a synthesis of theoretical frameworks and empirical findings, this paper aims to provide insights into optimizing teacher performance assessment to promote a more holistic, effective, and values-based educational system in Indonesia. Visual elements—including a diagram illustrating the conceptual framework, an image depicting an Indonesian classroom, and a comparative table of paradigms—are incorporated to enhance understanding and offer a multifaceted perspective